2012
DOI: 10.5713/ajas.2011.11312
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Probiotic and Prebiotic on Average Daily Gain, Fecal Shedding of Escherichia Coli, and Immune System Status in Newborn Female Calves

Abstract: Thirty two Holstein female calves (initial body weight = 40±3.0 kg) were used to investigate the effects of probiotic and prebiotic on average daily gain (ADG), fecal E. coli count, white blood cell count, plasma IgG1 level and cell-mediated immune response to injection of phytohemagglutinin in suckling female calves. Calves were assigned randomly to one of the four treatments, including whole milk without additives (control), whole milk containing probiotic, whole milk containing prebiotic and whole milk cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(32 citation statements)
references
References 39 publications
4
16
1
2
Order By: Relevance
“…The present results are supported by those obtained by Mohamadi and Dabiri (2012), who added probiotic to calves diets and observed significant improvement on FCR. These results were disagree with the findings of Riddell et al (2010) who reported a non-significant effect on FCR in calves fed bacterial probiotic treated diet.…”
Section: Discussionsupporting
confidence: 91%
“…The present results are supported by those obtained by Mohamadi and Dabiri (2012), who added probiotic to calves diets and observed significant improvement on FCR. These results were disagree with the findings of Riddell et al (2010) who reported a non-significant effect on FCR in calves fed bacterial probiotic treated diet.…”
Section: Discussionsupporting
confidence: 91%
“…Most of gram-negative bacteria attach to intestinal epithelium using specific mannose-fimbriae (Krol, 2011). Prebiotics in the colon are readily fermented by beneficial bacteria and produce VFA (Roodposhti & Dabiri, 2012), which may have bactericidal action against gramnegative bacteria (Ohland & MacNaughton, 2010). The similar results are reported in this experiment.…”
Section: Faecal Characteristicssupporting
confidence: 88%
“…Ghosh and Mehla (2012) reported the significant effect of MOS supplementation on DMI, ADG and FCE in crossbred calves. Corroborating the present investigation, Roodposhti and Dabiri (2012) showed that addition of probiotic, prebiotic and combination of these additives to milk enhanced ADG.…”
Section: Growth Performance Structural Growth Measurements and Nutsupporting
confidence: 81%
See 1 more Smart Citation
“…Prebiotics and probiotics are registered for use in cattle diets to improve performance [36,37,38]. Initially studies were focused upon inclusion of these materials in diets to increase milk production, average daily gains and overall improved delivery of replacement stock.…”
Section: Discussionmentioning
confidence: 99%